THE EFFECTS OF WORKERS PERCEPTION TOWARDS THE 2014 PENSION REFORM ACT (PRA) IN NIGERIA - Etebom, John Monday; Ogundare, Ogundare; Oluwakemi, Mary (CV The Journal Publishing, 2025)
This study examined the perception of workers towards the 2014 PRA. These were with a view to provide information on the satisfaction and opinion of workers towards 2014 PRA in Osun State. To facilitate the study, primary and secondary sources of data collection were adopted with qualitative content analysis technique for presentation of findings. “The study adopted System theory”. The study revealed there were gaps and loopholes in the PRA 2014 and its implementation which negatively altered the noble objectives of the reforms, thereby failed the yearning and expectations of workers and retirees respectively. The study concluded that satisfaction of workers toward 2014 Pension Reform Act in Osun State, Nigeria is negative, unhelpful and unsatisfactory. The study, therefore, suggested the need for further review and amendment of the provisions in the PRA, 2014 by the National Assembly (After 10 years of enactment) to take care of the identified loopholes and gaps in the Act. The study suggested the need for a sincere political will by the three tiers of government in Nigeria, and holistic synergy among the stakeholders to nurture the scheme to an enviable world Standard. The study further called for a strict compliance in implementation of the provisions of the Act (as amended)